1979
DOI: 10.1016/s0006-3495(79)85196-6
|View full text |Cite
|
Sign up to set email alerts
|

Complete neglect of differential overlap study of the binding of salts to N-methyl acetamide

Abstract: The complete neglect of differential overlap method is used to investigate the binding of LiF, LiCl, NaF, and NaCl to N-methyl acetamide (NMA) as a model for these ions binding to a peptide moiety. The cation (formula: see text) anion interaction is shown to result in a net residual charge on NMA, which becomes less positive as the difference in electronegativity between the anion and cation of the salt present increases. A residual charge of smaller magnitude is also found on a water molecule in the analogous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In other words, the interactions of the acetamide (−CO−NH−CH 3 ) groups with ions (cations and anions) can lead to a formation of coordinated complexes producing microdomains in solution as supported by several works. 21−23 Abdulnur and Laki have calculated optimal distance of approach for lithium cations to the oxygen atom on the MAc structure, which is close to d = 2.16 Å, 22 Additionally, they evaluated also the interaction energy of the Li + with MAc as ΔE = 346.9 kJ/mol. 22 These considerations can be used to explain the behavior of adsorption in the activated carbon as electrochemical double-layer capacitor material according to the pore size and shape as discussed below.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, the interactions of the acetamide (−CO−NH−CH 3 ) groups with ions (cations and anions) can lead to a formation of coordinated complexes producing microdomains in solution as supported by several works. 21−23 Abdulnur and Laki have calculated optimal distance of approach for lithium cations to the oxygen atom on the MAc structure, which is close to d = 2.16 Å, 22 Additionally, they evaluated also the interaction energy of the Li + with MAc as ΔE = 346.9 kJ/mol. 22 These considerations can be used to explain the behavior of adsorption in the activated carbon as electrochemical double-layer capacitor material according to the pore size and shape as discussed below.…”
Section: Methodsmentioning
confidence: 95%
“…21−23 Abdulnur and Laki have calculated optimal distance of approach for lithium cations to the oxygen atom on the MAc structure, which is close to d = 2.16 Å, 22 Additionally, they evaluated also the interaction energy of the Li + with MAc as ΔE = 346.9 kJ/mol. 22 These considerations can be used to explain the behavior of adsorption in the activated carbon as electrochemical double-layer capacitor material according to the pore size and shape as discussed below. The ionic bond in selected DESs based on LiX−MAc mixtures is a weakening process between LiX and MAc.…”
Section: Methodsmentioning
confidence: 95%
“…This formation of micro-domains is supported by several works dealing with infrared 39 and dielectric relaxation measurements 40 which have provided an estimation of this domain size in the (amide + salt) DES. For example, Abdulnur and Laki 41 shown that the cation-MAc-anion interactions in solution result in a net residual charge on MAc, which becomes less positive as the difference in charge density between the anion and the cation of the salt increases. Authors have then calculated the optimal distance of approach for lithium cations to the oxygen atom on the MAc structure, which is close to d = 2.16 Å, and the resultant electronic charge on MAc, obtained from Mulliken population analysis, is close to Q = +0.27.…”
Section: Physical Properties Of the Desmentioning
confidence: 99%
“…The strong interaction of the acetamide (-CO-NH-CH 3 ) groups with ions (cations and anions) can lead to the formation of coordinated complexes producing microdomains in solution as demonstrated by infrared and dielectric relaxation measurements. 25 The (N-H-O) hydrogen bond in the solvent explains the solid state of MAc at room temperature, by adding NaNO 3 the interaction between MAc and salt weakens or even breaks this intra (N-H-O) hydrogen bond due to the competitive Na + -O interactions in solution. With these new room temperature molten salt electrolytes, besides considering the applied voltage window in electrochemical systems like supercapacitors, the ion dimensions and solvent polarizability should also be considered.…”
Section: Electrochemical Studymentioning
confidence: 99%